THE MEGAPROJECT SPONSOR AS LEADER - Louw, Willem; Wium, Jan; Steyn, Herman; Gevers, Wim (South African Journal of Industrial Engineering, 2018)
The importance of the sponsor role, including its contribution to the success or failure of a project, is widely recognised in the project management literature. References to the sponsor’s leadership, and the substantial component it represents in the profile of the sponsor, are equally prevalent in the literature reviewed. A megaproject is a large-scale, complex venture that typically costs US$1 billion or more, takes many years to develop and build, involves multiple public and private stakeholders, is transformational, and influences millions of people. Executive sponsors are primarily allocated to projects of strategic importance that are complex, carry a considerable degree of risk, and are very visible. A megaproject is thus entitled to a sponsor from the executive (most senior) ranks within an organisation. Rather than joining the debates on complexity and leadership in the project management literature, this paper explains how leadership theories are used to identify instruments that can assist in the assessment of the leadership style and traits/attributes of a sponsor. A framework is then proposed to identify assessment instruments to evaluate the leadership style and leader traits/attributes of a project sponsor.